Manifestações linguísticas de crianças autistas: um estudo com foco no funcionamento multimodal. - Oliveira, Ádelly Kalyne da Silva (2023)
This research is based on the notion that language is multimodal and that the field of language acquisition is a productive axis for thinking about the place of the autistic child in the interaction through different linguistic manifestations, such as vocal production, gestures, and the plane of gaze. We sought to carry out the work in the light of the multimodal linguistic perspective, grounded in Kendon (2007, 2009, 2017), McNeill (2002, 2006), Cavalcante (2018), Cruz (2017, 2018a, 2018b), Fonte and Barros (2019), Fonte and Silva (2019) and among other authors. To dissolve theoretical and practical inquiries related to the role of gestuality in the dialectical axis, we launched a general objective: to analyze the gestural productions performed by autistic children in language acquisition from naturalistic contexts of interaction. Regarding methodology, audiovisual records of interactions — which took place in the Autistic Spectrum Study and Reception Group (GEAUT) from the Post-Graduation Program in Language Sciences (PPGCL) of the Catholic University of Pernambuco - were selected and collected from the database of the Language Practices Laboratory of PPGCL. This dissertation is a descriptive work of the case study type, as it involves the specificity of autism. The research participants are four autistic children. They are in the process of language acquisition: one child is female (Lara), and three children are male (Igor, Caio, and Pedro). For the selection of the interactive scenes, we established as criteria contexts that present: i) gestural production by autistic children; ii) gestures that exhibit roles in the multimodal discourse of autistic children; iii) the interactive relationship between autistic child and interlocutor(s) in diversified contexts of linguistic unfoldings. We used the software Eudico Language Annotator (ELAN) for data transcription. The program is of utmost relevance, as it enables the creation of trails, the annotation, organization, and visualization of data. With the platform, we explored the following language planes of the children and the interlocutors: gesture plane, vocal plane, and gaze plane. We observed the different linguistic movements performed by autistic children from the study's results, and we noticed the multimodal productions engendered in the children's subjective practice. For illustration, there was the production of the emblem, the flapping movement, the deictic gesture, and the iconic gesture by Igor. Lara, in turn, produced emblems and used the deictic gesture and the gestural mix. As for Caio, he used the emblem and peculiarly produced a deictic gesture. As for Pedro, he contemplated the emblem, and the deictic gesture was present in the child's discursive practice. Through the data, we see the relationship between multimodal elements in the linguistic production of autistic children. With the research, we observe that gesture is not an accessory element. It is language itself, a way that the autistic person can use to be in language and make herself understood by the other person. Reflecting on the different linguistic manifestations of autistic children in the acquisition process favors the understanding of gestures as a means of sharing meanings and constitution of a subject that produces a language through the voice, gestures, and look; processes of language that need to be considered, beyond the margins, within linguistic studies.